COMPUTER ANALYSIS OF THE UNDERLYING EQUILIBRIUM MODELS WITH PUBLIC GOOD - Y. Gavrilets; I. Tarakanova (Вестник университета)
This article discusses an option of the mathematical model of economic situations with public goods consumed by several market participants simultaneously. Computer analysis of this model was performed by using the MATHCAD package which allows toillustrate some techniques of determining of market balance. It was assumed that the participants, considering the choice of the other is equal to their previous decision, comes to the agreed result in finish.